Research of High-voltage Impulse Track Circuit Receiver Based on Software-Algorithms - He Wenjuan; Ren Jianxin; He Tao; Wei Zongshou; Wang Ruidong (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper aims to design a type of track receiver that relies on software algorithms and to optimize the whole structure of the track receiver. A voltage sensor is placed between the sender and receiver in a track circuit to collect high-voltage pulse signals generated by the sender. These signals are then sent to the CPU of the receiver for software operation. At the same time, the receiver also collects the high-voltage pulse signals from the track circuit. First, the Butterworth Low-Pass filters out 50Hz traction current of the pulse signals. These signals are the outputs from two different types of operating CPUs. Consequently, the main goal of this paper is to successfully design two sets of CPUs that respectively adopt two types of software algorithms, FFT and Mallat. It will be proven that this improved scheme has possibly reached the qualities of high speed and accuracy of CPU operation, and obviously improves instantaneity and reliability. It has been shown that this scheme, which is more feasible, has a higher degree of automation and is easier to maintain than the original equipments practically used. Hence, the scheme has the possibility of owning a much brighter application prospect in the future. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3616